On Fibonacci Functions with Period - Banyat Sroysang (Discrete Dynamics in Nature and Society)
A function is said to be a Fibonacci function if for all . In 2012, some properties on the Fibonacci functions were presented. In this paper, for any positive integer , a function is said to be a Fibonacci function with period if for all ; we present some properties on the Fibonacci functions with period .